Assessing fecal contamination from human and environmental sources using Escherichia coli as an indicator in rural eastern Ethiopian households—a cross-sectional study from the EXCAM project - Deblais, Loïc; Ahmedo, Belisa Usmael; Ojeda, Amanda; Mummed, Bahar; Wang, Yuke; Mekonnen, Yitagele Terefe; Demisie Weldesenbet, Yenenesh; Hassen, Kedir A.; Brhane, Mussie; McKune, Sarah; Havelaar, Arie H.; Liang, Song; et al. (Frontiers in Public Health, 2025)
IntroductionEnteric pathogens are a leading causes of diarrheal deaths in low-and middle-income countries. The Exposure Assessment of Campylobacter Infections in Rural Ethiopia (EXCAM) project, aims to identify potential sources of bacteria in the genus Campylobacter and, more generally, fecal contamination of infants during the first 1.5 years of life using Escherichia coli as indicator.MethodsA total of 1,310 samples (i.e., hand rinses from the infant, sibling and mother, drinking and bathing water, food and fomite provided to or touched by the infants, areola swabs, breast milk and soil) were collected from 76 households between May 2021 and June 2022. Samples were assigned to two groups by infant age: TP1 (time point 1), infants between 4 and 8 months of age, and TP2, infants between 11 and 15 months of age. Fluorometric and semi-selective colorimetric approaches were used to quantify E. coli in the field samples.ResultsOverall, E. coli was ubiquitous within selected households (56.8% across the study). E. coli was more frequently detected than average (>53%) with high concentration (>2-log CFU) in soil (g) and per pair of hand, while the opposite trend (<33%; <1.5-log CFU) was observed in food provided to the infants (g or mL), per areola, and breast milk (mL; p < 0.01). E. coli was frequently detected in fomites touched by the infants, drinking and bathing water (>51%), but at low concentration (<1.5-log CFU). Correlation analysis between E. coli concentration in different sample types suggested that the mother’s hands and fomites might play a key role in the transmission of E. coli to the infants (p < 0.01; r2 > 0.3).DiscussionUsing E. coli as surrogate, our study identified mother (hands and areola) as reservoirs likely to be involved in frequent transmission of fecal contaminants to infants within rural Ethiopian households.